Softening and structural instability mechanism of biodegradable Zn-0.45Mn alloy at different heat treatment temperatures. (December 2022) - Ding, Feng; Zhu, Xinglong; Guo, Pushan; Yang, Lijing; Zhang, Qingke; Xu, Cheng; Zhang, Yi; Sun, Wensheng; Song, Zhenlun
Abstract: The major effects and mechanism of heat-treatment on the mechanical properties and microstructures of biodegradable Zn-0.45Mn alloys were investigated. Results showed that Zn-0.45Mn exerted an obvious softening effect after heat treatment (240 ℃, 300 ℃, 350 ℃). Stress strain curves showed that the tensile strength decreased from 223.21 ± 2.41 MPa to 105.47 ± 2.43 MPa and the plasticity initially increased and then decreased. The alloy in HT300 state showed suitable softening and weakening effects and was easily processed into wire. The causes of the changes were analyzed through microstructural characterization and statistics, and the structural instability caused by recrystallization was also discussed. Notably, the secondary recrystallization resulted in abnormally large grains and considerably decreased plasticity of the alloy. Graphical Abstract: ga1